Analisis Korelasi Kecerdasan Emosional dengan Kepercayaan Diri Pada Mahasiswa - Nur Anisa; Andri Purwandari (Universitas Malahayati, 2023)
ABSTRACT Emotional intelligence affects the self-confidence of each individual. Everyone has different self-confidence and emotional intelligence. An individual who feels confident will have high emotional intelligence. Knowing the relationship between emotional intelligence and self-confidence in students. This research is quantitative with a cross-sectional research design. The population in this study was 118 undergraduate nursing students in semesters VI and VIII. This sampling technique is stratified random sampling and statistical tests using the Pearson Test. Emotional intelligence is mostly in the high category (74.7%), with self-confidence in the good category (100%). The results of the Pearson test show that the significance value is p=0.000<0.05, and the correlation coefficient is 0.413. There is a relationship between emotional intelligence and self-confidence in students of the Nursing Study Program (S1). Keywords: Emotional Intelligence, Self Confidence ABSTRAK Kecerdasan emosional mempengaruhi kepercayaan diri setiap individu. Setiap orang memiliki kepercayaan diri dan kecerdasan emosional yang berbeda-beda. Sebagai individu yang merasa penuh percaya diri akan memiliki kecerdasan emosonal yang tinggi. Tujuan untuk mengetahui hubungan kecerdasan emosional dengan kepercayaan diri pada mahasiswa. Penelitan ini bersifat kuantitatif dengan rancangan peneltian cross sectional. Populasi dalam penelitian ini adalah mahasiswa prodi keperawatan S1 semester VI dan VIII yang berjumlah 118 orang. Teknik pengambilan sampel ini adalah stratified random sampling dan uji statistik menggunakan Uji Pearson. Kecerdasan Emosional sebagian besar dalam kategori tinggi (74,7,%), dengan Kepercayaan Diri dalam kategori baik (100 %). Hasil uji Pearson menujukkan bahwa nilai signifikansi p=0,000<0,05, correlation coefisient 0,413. Ada hubungan antara kecerdasan emosional dengan kepercayaan diri pada mahasiswa prodi keperawatan (S1). Kata Kunci : Kecerdasan Emosional, Kepercayaan Diri